(untitled) (Reumatismo, 2004)
Osteonecrosis is a disease characterized by the death of marrow and bone tissues. All bones may be affected, most commonly those of the hip, knee, shoulder, ankle as well as the small bones of the hands and feet. When the disease involves a weight-bearing joint there is a significant risk that subarticular fracture may develop leading to disabling arthrosis and requiring, therefore, arthroplasty surgery. Osteonecrosis typically affects patients in their third, fourth and fifth decades of life and is associated with many factors including other diseases and co-morbidities. Multifocal osteonecrosis is defined according to the involvement of at least three separated anatomic sites. We describe the case of a young man with osteonecrosis of the shoulder and hip joints which required total arthroplasty. Among biochemical investigations, an increase in the plasminogen activator inhibitor type 1 (PAI-1) levels associated with mild hyperhomocysteinemia was present. Another finding was the HLA B27, without signs of spondyloarthropathies. In patients with osteonecrosis, especially if multifocal, a careful medical history, a complete physical examination and some biochemical investigations, particularly those related to thrombophilia and hypofibrinolysis, should be performed.